Spontaneous CO Release from RuII(CO)2–Protein Complexes in Aqueous Solution, Cells, and Mice1. Issue 4 (4th December 2014) - Chaves‐Ferreira, Miguel; Albuquerque, Inês S.; Matak‐Vinkovic, Dijana; Coelho, Ana C.; Carvalho, Sandra M.; Saraiva, Lígia M.; Romão, Carlos C.; Bernardes, Gonçalo J. L.
Abstract We demonstrate that RuII(CO)2–protein complexes, formed by the reaction of the hydrolytic decomposition products of [fac‐RuCl(κ2‐H2NCH2CO2)(CO)3] (CORM‐3) with histidine residues exposed on the surface of proteins, spontaneously release CO in aqueous solution, cells, and mice. CO release was detected by mass spectrometry (MS) and confocal microscopy using a CO‐responsive turn‐on fluorescent probe. These findings support our hypothesis that plasma proteins act as CO carriers after in vivo administration of CORM‐3. CO released from a synthetic bovine serum albumin (BSA)–RuII(CO)2 complex leads to downregulation of the cytokines interleukin (IL)‐6, IL‐10, and tumor necrosis factor (TNF)‐α in cancer cells. Finally, administration of BSA–RuII(CO)2 in mice bearing a colon carcinoma tumor results in enhanced CO accumulation at the tumor. Our data suggest the use of RuII(CO)2–protein complexes as viable alternatives for the safe and spatially controlled delivery of therapeutic CO in vivo.